2001
DOI: 10.1152/jn.2001.86.4.1869
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Evidence for a Chemotopy of Biologically Relevant Odors in the Olfactory Bulb of the Channel Catfish

Abstract: Extracellular electrophysiological recordings from single olfactory bulb (OB) neurons in the channel catfish, Ictalurus punctatus, indicated that the OB is divided into different functional zones, each processing a specific class of biologically relevant odor. Different OB regions responded preferentially at slightly above threshold to either a mixture of 1) bile salts (10(-7) to 10(-5) M Na(+) salts of taurocholic, lithocholic, and taurolithocholic acids), 2) nucleotides [10(-6) to 10(-4) M adenosine-5'-triph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 73 publications
6
68
0
Order By: Relevance
“…These two independent methods therefore confirm for Manduca that different classes of odorants are represented as overlapping but distinct spatial patterns of activity in the AL glomeruli. Accumulating evidence from the vertebrate OB (Rubin and Katz, 1999;Fuss and Korsching, 2001;Nikonov and Caprio, 2001) and insect AL (Gao et al, 2000;Vosshall et al, 2000;Galizia and Menzel, 2001) also supports this combinatorial spatial model.…”
Section: Discussionmentioning
confidence: 75%
“…These two independent methods therefore confirm for Manduca that different classes of odorants are represented as overlapping but distinct spatial patterns of activity in the AL glomeruli. Accumulating evidence from the vertebrate OB (Rubin and Katz, 1999;Fuss and Korsching, 2001;Nikonov and Caprio, 2001) and insect AL (Gao et al, 2000;Vosshall et al, 2000;Galizia and Menzel, 2001) also supports this combinatorial spatial model.…”
Section: Discussionmentioning
confidence: 75%
“…Studies using calcium imaging (Friedrich and Korsching, 1997;Friedrich and Korsching, 1998) and physiological recording (Nikonov and Caprio, 2001), to characterize the activity patterns elicited in the olfactory bulb by amino acids and bile salts, have demonstrated that the medial regions of the bulb process bile salt input and the lateral regions amino acids and nucleotides. This chemotopy, which appears to separate the processing of feeding cues (amino acids) from social cues (bile salts), is present in both channel catfish (Nikonov and Caprio, 2001;Nikonov et al, 2005) and zebrafish (Friedrich and Korsching, 1998). Thus the loss of behavioral responses to the amino acids but not taurocholic acid in the lre mutant suggests that the defect may result in part from the disruption and or loss of the sensory fibers in the lateral chain of glomerular modules that respond to amino acids.…”
Section: Segregation Of Physiological Responses Accompanies Distinct mentioning
confidence: 99%
“…In this ex vivo preparation, the lateral region of the lamprey olfactory bulb was a locus for amino acid responses and the dorsal region of the sea lamprey olfactory bulb responded to the steroid bile acid taurocholic acid in all cases, to both taurocholic acid and the steroid pheromones in 30% of cases, and to amino acids, taurocholic acid and pheromones in 50% of cases, and was the only region with cases that responded to taurocholic only (20%). Amino acids activate the lateral olfactory bulb region in teleost fish (Hansen et al, 2003;Hara and Zhang, 1998;Fujita et al, 1991;Hara, 2001, 2004;Friedrich and Korsching, 1998;Nikonov and Caprio, 2001) and in the larval stage of the amphibian Xenopus laevis (Gliem et al, 2013). However, while the olfactory system in teleosts responds to a wide variety of basic, acidic and aromatic amino acids (Hansen et al, 2003;Laberge and Hara, 2001), the lamprey olfactory system responds only to basic amino acids (Li et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, while the olfactory system in teleosts responds to a wide variety of basic, acidic and aromatic amino acids (Hansen et al, 2003;Laberge and Hara, 2001), the lamprey olfactory system responds only to basic amino acids (Li et al, 1995). In teleosts, primarily bile acids and sex pheromones activate glomeruli in the medial region (Hansen et al, 2003;Hara et al, 1998;Fujita et al, 1991;Hara, 2001, 2004;Friedrich and Korsching, 1998;Nikonov and Caprio, 2001). In Xenopus, sulphated steroids stimulate the dorsal and medial region of the main olfactory system, rather than the lateral region (Sansone et al, 2015).…”
Section: Discussionmentioning
confidence: 99%